Clinical Practice Guideline: Bell's Palsy Executive Summary. Issue 5 (4th November 2013) - Baugh, Reginald F.; Basura, Gregory J.; Ishii, Lisa E.; Schwartz, Seth R.; Drumheller, Caitlin Murray; Burkholder, Rebecca; Deckard, Nathan A.; Dawson, Cindy; Driscoll, Colin; Gillespie, M. Boyd; Gurgel, Richard K.; Halperin, John; et al.
Abstract : The American Academy of Otolaryngology—Head and Neck Surgery Foundation (AAO‐HNSF) has published a supplement to this issue featuring the new Clinical Practice Guideline: Bell's Palsy. To assist in implementing the guideline recommendations, this article summarizes the rationale, purpose, and key action statements. The 11 recommendations developed encourage accurate and efficient diagnosis and treatment and, when applicable, facilitate patient follow‐up to address the management of long‐term sequelae or evaluation of new or worsening symptoms not indicative of Bell's palsy. There are myriad treatment options for Bell's palsy; some controversy exists regarding the effectiveness of several of these options, and there are consequent variations in care. In addition, there are numerous diagnostic tests available that are used in the evaluation of patients with Bell's palsy. Many of these tests are of questionable benefit in Bell's palsy. Furthermore, while patients with Bell's palsy enter the health care system with facial paresis/paralysis as a primary complaint, not all patients with facial paresis/paralysis have Bell's palsy. It is a concern that patients with alternative underlying etiologies may be misdiagnosed or have an unnecessary delay in diagnosis. All of these quality concerns provide an important opportunity for improvement in the diagnosis and management of patients with Bell's palsy.